Impact of Organic and Conventional Systems of Coffee Farming on Soil Properties and Culturable Microbial Diversity - Kulandaivelu Velmourougane (Scientifica)
A study was undertaken with an objective of evaluating the long-term impacts of organic (ORG) and conventional (CON) methods of coffee farming on soil physical, chemical, biological, and microbial diversity. Electrical conductivity and bulk density were found to increase by 34% and 21%, respectively, in CON compared to ORG system, while water holding capacity was found decreased in both the systems. Significant increase in organic carbon was observed in ORG system. Major nutrients, nitrogen and potassium, levels showed inclination in both ORG and CON system, but the trend was much more pronounced in CON system. Phosphorus was found to increase in both ORG and CON system, but its availability was found to be more with CON system. In biological attributes, higher soil respiration and fluorescein diacetate activity were recorded in ORG system compared to CON system. Higher soil urease activity was observed in CON system, while dehydrogenase activity does not show significant differences between ORG and CON systems. ORG system was found to have higher macrofauna (31.4%), microbial population (34%), and microbial diversity indices compared to CON system. From the present study, it is accomplished that coffee soil under long-term ORG system has better soil properties compared to CON system.